EFEK TERATOGENIK DEKOKTA DAUN NIMBA (Azadirachta indica A. Juss.) TERHADAP DAYA TETAS DAN LUAS AREA YOLK SAC PADA EMBRIO IKAN ZEBRA (Danio rerio) - Anisa Armadani (Jurnal Kedokteran Komunitas, 2018)
Introduction: Neem leaf has many uses, but not yet known the toxic effects especially on fetal growth and development. Therefore, it is necessary to carry out the teratogenic test of neem leaves decocta (NLD) to assess the safety of neem leaves in pregnancy conditions by observing hatchability and yolk sac area of zebrafish embryos.Methods: Zebrafish embryos were divided into 5 groups, control (P0), NLD therapeutic dose 20 μg/mL (P1), NLD ½ MATC dose 61 μg/mL (P2), NLD MATC dose 123 μg/mL (P3), and NLD LC50 dose 260 μg/mL (P4). The LC50 dose is obtained through a range-finding doses which will be determined from the death of 50% of the sample, while the MATC dose is obtained through the formula √???????????????? ???? ????????????????2. The number of samples in each group for hatchability variables is 10 embryos and the yolk sac area variable is 5 samples. The exposure was done when the embryo was 5.25 hpf (hour post fertilization) up to 72 hpf and then observed under a stereo microscope with 4.5x magnification that has connected to a computer. For hatchability variables, the treatment was repeated 3 times, while for the yolk sac area variable was done once. Hatchability was calculated using the Hogendoorom method, while the measurement of the yolk sac area used Image J software. Value is considered significant if p<0.05.Results: NLD exposure in all groups did not cause a significant decrease in zebrafish embryo hatchability, although there was a trend of decreasing hatchability in the P4 group by 10% compared to P0. NLD exposure on group P1 did not significantly increase the yolk sac area compared to P0, while NLD exposure in group P2, P3 and P4 can significantly increase the yolk sac area by 12.5%, 17%, and 25% compared to P0.Conclusion: The increase in dosage of NLD did not affect changes in hatchability but there was an increase in the yolk sac area of zebrafish embryos.